The motility regulator flhDC drives intracellular accumulation and tumor colonization of Salmonella. Issue 1 (12th February 2019) - Raman, Vishnu; Van Dessel, Nele; O'Connor, Owen M.; Forbes, Neil S.
Abstract : Background: Salmonella have potential as anticancer therapeutic because of their innate tumor specificity. In clinical studies, this specificity has been hampered by heterogeneous responses. Understanding the mechanisms that control tumor colonization would enable the design of more robust therapeutic strains. Two mechanisms that could affect tumor colonization are intracellular accumulation and intratumoral motility. Both of these mechanisms have elements that are controlled by the master motility regulator flhDC . We hypothesized that 1 ) overexpressing flhDC in Salmonella increases intracellular bacterial accumulation in tumor cell masses, and 2) intracellular accumulation of Salmonella drives tumor colonization in vitro . Methods: To test these hypotheses, we transformed Salmonella with genetic circuits that induce flhDC and express green fluorescent protein after intracellular invasion. The genetically modified Salmonella was perfused into an in vitro tumor-on-a-chip device. Time-lapse fluorescence microscopy was used to quantify intracellular and colonization dynamics within tumor masses. A mathematical model was used to determine how these mechanisms are related to each other. Results: Overexpression of flhDC increased intracellular accumulation and tumor colonization 2.5 and 5 times more than control Salmonella, respectively (P < 0.05). Non-motile Salmonella accumulated in cancer cells 26 times less than controls (P < 0.001). Minimally invasive, ΔsipB, Salmonella colonized tumor masses 2.5 times less than controls (P < 0.05). When flhDC was selectively induced after penetration into tumor masses, Salmonella both accumulated intracellularly and colonized tumor masses 2 times more than controls (P < 0.05). Mathematical modeling of tumor colonization dynamics demonstrated that intracellular accumulation increased retention of Salmonella in tumors by effectively causing the bacteria to bind to cancer cells and preventing leakage out of the tumors. These results demonstrated that increasing intracellular bacterial density increased overall tumor colonization and that flhDC could be used to control both. Conclusions: This study demonstrates a mechanistic link between motility, intracellular accumulation and tumor colonization. Based on our results, we envision that therapeutic strains of Salmonella could use inducible flhDC to drive tumor colonization. More intratumoral bacteria would enable delivery of higher therapeutic payloads into tumors and would improve treatment efficacy.